PENGARUH KUALITAS PELAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN - Ade Nurhayati; Nuni Nurhalimah (Eqien - Jurnal Ekonomi dan Bisnis, 2019)
Business continuity (going concern) is the main purpose of a business entity since the establishment of the business entity is closely related to how management can manage the business both from financial factors and non-financial factors.This research was conducted to find out what things can affect customer satisfaction in a purchase. In this research used two independent variable of service quality (X1) and customer value (X2), while customer satisfaction (Y) as dependent variable. Based on the results of the analysis, found that both independent variables have a significant and positive effect on the dependent variable. Service quality variable has positive effect 0,425 with significance level 0,003. The customer value variable has a positive effect of 0.486 with a significance level of 0.000. Adjusted R Square of the three variables is 23.7 percent, which means that the two independent variables are able to explain the variation in the dependent variable of 23.7 percent with 76.3 percent explained by other variables not used in this study.